KONVERSI AGAMA DAN INTERAKSI KOMUNITAS MUALLAF DI DENPASAR - Aziz, Ahmad Amir; Hidayat, Nurul (JURNAL PENELITIAN KEISLAMAN, 2010)
The number of Muslims in Bali has dramatically increased in the last decades. In addition to the high rate of migration of Muslims from other regions to Bali, the conversion of Balinese into Islam has triggered the growth of Muslim population in the island. This study aims to describe analytically the background and the process of Hindu conversion to Islam in Denpasar, Bali. The study also examines the pattern of interaction of the converts with their family, their previous congregation and with their new fellow Muslims. The data collection in this phenomenological study was gathered through observation, interviews with the converts, visits to the convert counseling and guidance centers and documentation. The study finds that there are various reasons for Hinduâs conversion to Islam. Each informant has distinct personal characters and comes from variegated social backgrounds. The first motivation of conversion is affection, followed by intellectual and transcendental impulses. Not all converts receive discrimination from their family. Only those who stem from the high caste may encounter disfavor from their family. However, the converts are easily accepted by their family and new community if they can make a fundamental contribution to the both sides.